1997
DOI: 10.1007/s001250050759
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between insulin-mediated glucose disposal and regulation of plasma and adipose tissue lipoprotein lipase

Abstract: Lipoprotein lipase plays a key role in the catabolism of triglyceride(TG)-rich lipoproteins [1], and it is generally accepted that the activity of this enzyme is decreased in insulin-deficient states [2][3][4]. While alterations in LPL have long been suspected in insulin resistance [1,5], the situation concerning the relationship between LPL and insulin-mediated glucose disposal is more complicated. Patients with non-insulin-dependent diabetes mellitus are generally assumed to be insulin resistant [6,7], and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 56 publications
1
46
1
1
Order By: Relevance
“…However, it is known that the activity of lipoprotein lipase (LPL), the enzyme that clears TG from the circulation, is higher in blacks than whites. 43 In addition, even though insulin resistance should impair LPL activity, 44 we have previously shown that LPL activity does not decline in insulin-resistant African Americans. 45 …”
Section: Discussionmentioning
confidence: 95%
“…However, it is known that the activity of lipoprotein lipase (LPL), the enzyme that clears TG from the circulation, is higher in blacks than whites. 43 In addition, even though insulin resistance should impair LPL activity, 44 we have previously shown that LPL activity does not decline in insulin-resistant African Americans. 45 …”
Section: Discussionmentioning
confidence: 95%
“…For example, it has been shown that LPL mRNA increase significantly in brown adipose tissue after insulin injection to fasting rats [46]. On the other hand, LPL activity is reduced under insulin resistance state because the ability of insulin to up-regulate LPL gene is impaired in insulin resistant individuals, leading to hypertriglyceridemia [47]. It is conceivable that insulin differentially affects the allele-specific effect of the HindIII polymorphism in individuals with different state of insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Even though we did not measure the lipoprotein lipase mass, it is likely that weight loss induced a decrease AT-LPL activity of women through postranslational mechanisms, as already documented. 9,11,46 Finally, it is well known that a substantial part of HDL is derived from surface constituents of chylomicrons and VLDL during breakdown of their triglycerides by lipoprotein lipase. 47,48 In this regard, Magill et al 49 have already observed that a high gluteal AT-LPL activity increased the fractional rate of catabolism of VLDL, which, in turn, raised HDL-C concentrations.…”
Section: Discussionmentioning
confidence: 99%